Does the Volatility of Macroeconomic Variables Depress The Profitability of Islamic Banking? - Widarjono, Agus (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
Islamic banking in Indonesia has been growing rapidly since 2010. The profitability of Islamic bank depends on Islamic bank characteristics and macroeconomic condition. As a country with an open economy, macroeconomic conditions are very volatile. Through the theory of exchange rate pass through, the exchange rate fluctuation affects domestic prices so that it affects the profits of Islamic bank. This study analyzes the impact of the instability of the macroeconomic variables, namely the exchange rate and inflation on the profitability of Islamic bank. The instability of inflation and exchange rate are measured using the GARCH (Generalized Autoregressive Conditional Heteroskedasticity). This study applies ARDL (Autoregressive Distributed Lag Model). The data used is monthly data starting from January 2011 to June 2018. The results of the study show that the exchange rate and inflation instability depress the profitability of Islamic banki. More interestingly, instability of inflation has a greater negative impact than the instability of exchange rate on Islamic bank profit. The most Islamic bank characteristics influencing Islamic banking profit was bad financing as known as a non performing financing (NPF).